Study on post-traumatic stress disorder and influencing factors in adult ICU patients on mechanical ventilation using latent profile analysis: a cross-sectional survey - Li, Yunting; Yuan, Xiaoli; Liu, Mi; Xiong, Yan; Zhang, Jiabi (Frontiers in Psychology, 2025)
ObjectiveThis study aimed to explore the potential classification and influencing factors of post-traumatic stress disorder (PTSD) in intensive care unit (ICU) patients receiving mechanical ventilation to provide a theoretical basis for formulating targeted intervention measures.MethodsA total of 229 patients on mechanical ventilation who were hospitalized in the intensive care unit of a Class III Grade A hospital in Zunyi from August 2023 to July 2024 were selected as research participants using a purposive sampling method. The General information questionnaire, Eysenck Personality Questionnaire Revised, Short Scale for Chinese (EPQ-RSC), Simplified Coping Style Questionnaire (SCSQ), Perceived Social Support Scale (PSSS), and Hospital Anxiety and Depression Scale (HADS) were used to assess the patients within 7 days after discharge from the ICU. One month after extubation, a cross-sectional survey was conducted using the Impact of Event Scale-Revised (IES-R). Latent profile analysis (LPA) was used to analyze the latent subtypes of PTSD, and univariate analysis and a disordered multivariate logistic regression model were used to evaluate the influencing factors associated with different types of PTSD.ResultsA total of 215 valid questionnaires were collected, and the effective recovery rate was 93.89%. The incidence of PTSD was 14.9% (95% CI: 10.12%−19.64%). There were three latent categories of PTSD among the ICU patients on mechanical ventilation: the “low-stress group” (56.8%, n = 112), the “medium-stress group” (31.6%, n = 68), and the “high-stress group” (11.6%, n = 25). Multinomial logistic regression analysis, using the low-stress group as the reference, identified that higher educational attainment (OR [95% CI]: 1.359 [1.172–1.576], p < 0.001) and elevated scores on the Hospital Anxiety and Depression Scale (OR [95% CI]: 1.447 [1.186–11.767], p < 0.001) were statistically significant predictors of membership in the medium- and high-stress groups.ConclusionPTSD symptoms among mechanically ventilated ICU survivors manifest in three distinct profiles. Our findings strongly recommend early psychological screening, particularly focusing on anxiety and depression levels and patients' educational background. Medical staff should formulate targeted intervention plans based on the characteristics of different patient categories to lower the level of PTSD in patients.